2022
DOI: 10.3390/foods11182873
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Choices and Habits Related to Tea Consumption by Poles

Abstract: Tea is one of the most consumed beverages in the world. In the literature, much attention is paid to the influence of tea and its components on human health and consumer purchasing behavior. The aim of the study was to analyze the habits of Polish consumers regarding tea consumption, brewing methods, and their choices related to tea, to describe the characteristics of tea consumers, and present their segmentation based on consumer choices and habits regarding tea consumption. The study was performed using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Consumer choices can be influenced by various factors such as socio-demographics, traditions, health benefits, and taste, as well as drivers of consumption trends [ 25 , 27 , 32 , [51] , [52] , [53] , [54] , [55] ]. Consistent with these studies, our findings revealed that consumers' age had influence their preferences for the type of THIs beverages.…”
Section: Discussionmentioning
confidence: 99%
“…Consumer choices can be influenced by various factors such as socio-demographics, traditions, health benefits, and taste, as well as drivers of consumption trends [ 25 , 27 , 32 , [51] , [52] , [53] , [54] , [55] ]. Consistent with these studies, our findings revealed that consumers' age had influence their preferences for the type of THIs beverages.…”
Section: Discussionmentioning
confidence: 99%
“…Hydria respondents frequently consume mountain tea (61.2%), black tea (60.3%), sage (59.4%), and mixed herbal tea (58.4%) at home most during breakfast, while chamomile is used mainly during the afternoon or dinner or night (54.2%). On the contrary, Polish consumers prefer black, green, and flavored tea mostly at home and between meals (67.3%), as well as during the first breakfast (62.2%) and dinner (48.5%) [ 77 ]. The differences in moment consumption during the day depend on the kind of herbal infusions/decoctions and tea and might be associated with their health effects, consumers’ habits/preferences, and the country’s culture.…”
Section: Discussionmentioning
confidence: 99%
“…We have an idea why that might be the case. In the first place, black tea remains the most popular production style among all consumer segments in high income Western Countries like Poland (Czarniecka-Skubina et al 2022). Green tea also cannot produce sustained or nuanced flavor over multiple infusions, nor is there much meaningful diversity in green tea aromas.…”
Section: Practical Implicationsmentioning
confidence: 99%